The The Effect of Work Motivation, Training and Employee Development on Employee Performance with Job Satisfaction as a Mediating Variable - Farras, Juan; Iqbal, M. Ali (International Journal of Social and Management Studies, 2025)
Basically, this study aims to examine and analyse the importance of work motivation and employee training and development on employee performance by using job satisfaction variables as mediating variables at PT Tower Bersama Group. By using quantitative research design with explanatory survey method, namely data collection using a questionnaire with Likert scale model. Data sampling of organic employee respondents as many as 130 respondents. Structural Equation Modeling (SEM) PLS Version 4.1 is used as a tool for processing data. In this study using four variables, twenty dimensions and forty-four indicators. From the results of this study it can be concluded that all variables have a significant effect on employee performance, namely: 1) Work motivation on employee performance. 2) Employee training and development on employee performance, 3) Job satisfaction on employee performance, 4) Work motivation on job satisfaction, 5) Employee training and development on employee performance, 6) Job satisfaction mediates the effect of work motivation on employee performance, 7) Job satisfaction mediates the effect of employee training and development on employee performance. Keywords: Work Motivation, Employee Training and Development, Job Satisfaction, Employee Performance